Characterization of Reflexivity by Convex Functions. (17th July 2016) - Luo, Zhenghua; Cheng, Qingjin
Abstract : A new convexity property of convex functions is introduced. This property provides, in particular, a characterization of the class of reflexive Banach spaces.